2017
DOI: 10.1016/j.jacep.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Resting and Exercise-Induced Left Atrial Hypertension in Patients With Atrial Fibrillation

Abstract: Presence of either resting or exercise-induced LAH identified AF patients with a distinct clinical profile, extensive LA substrate, and different clinical response to catheter ablation. Stratification of AF patients based on the LA exercise hemodynamics could help in the future to tailor the ablation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
3
23
0
3
Order By: Relevance
“…In our study, apelin levels also statistically signifi cantly correlated inversely with left atrial (LA) size, left ventricular diastolic diameter and duration of AF, which might be indirect markers of chronically increased LA stretch. According to our knowledge, this was not studied before, but research from Sramko et al suggested that an increased left atrial pressure in the patients with AF regardless if measured in sinus rhythm was associated with an extensive LA arrhythmogenic substrate (26). Whether patients with paroxysmal AF have chronically increased LA pressure even in sinus rhythm and therefore decreased apelin concentrations merits further research.…”
Section: Discussionmentioning
confidence: 85%
“…In our study, apelin levels also statistically signifi cantly correlated inversely with left atrial (LA) size, left ventricular diastolic diameter and duration of AF, which might be indirect markers of chronically increased LA stretch. According to our knowledge, this was not studied before, but research from Sramko et al suggested that an increased left atrial pressure in the patients with AF regardless if measured in sinus rhythm was associated with an extensive LA arrhythmogenic substrate (26). Whether patients with paroxysmal AF have chronically increased LA pressure even in sinus rhythm and therefore decreased apelin concentrations merits further research.…”
Section: Discussionmentioning
confidence: 85%
“…The association of hypertension and arrhythmogenic atrial remodelling requiring substrate modification has been shown in previous studies [ 24 ]. In line with this finding, patients with increased LA pressures, as often associated with HTN, also display more extensive arrhythmogenic substrate and higher rates of arrhythmia recurrence [ 25 ]. After successful AF ablation, patients with elevated LA pressure seem to show a greater benefit regarding quality of life than patients without LA pressure elevation [ 25 ].…”
Section: Discussionmentioning
confidence: 87%
“…In line with this finding, patients with increased LA pressures, as often associated with HTN, also display more extensive arrhythmogenic substrate and higher rates of arrhythmia recurrence [ 25 ]. After successful AF ablation, patients with elevated LA pressure seem to show a greater benefit regarding quality of life than patients without LA pressure elevation [ 25 ]. However, whether the direct hemodynamic effects of HTN by elevated atrial strain and atrial pressure or indirect influences by HTN-promoted cardiac comorbidities play the leading role for atrial remodelling has to be evaluated in experimental studies aimed at mechanistic analyses.…”
Section: Discussionmentioning
confidence: 87%
“…[ 10 ] These comorbidities have been associated with increased LA pressure in AF patients. [ 41 ] Hypertension is associated with abnormalities in the RAAS with high circulating levels of angiotensin II, ACE, and aldosterone. In addition to the fibrotic mechanism previously discussed, these components contribute to atrial myopathy by affecting ion channel structure and function and cause pro-inflammatory effects on the LA.…”
Section: Pathophysiology Of Atrial Myopathymentioning
confidence: 99%